Crystallization and preliminary crystallographic analysis of BbCRASP-1, a complement regulator-acquiring surface protein of Borrelia burgdorferi - Cordes, Frank; Kraiczy, Peter; Roversi, Pietro; Skerka, Christine; Kirschfink, Michael; Simon, Markus M.; Brade, Volker; Lowe, Edward D.; Zipfel, Peter F.; Wallich, Reinhard; Lea, Susan M. (Acta crystallographica. Section D, Biological crystallography, 2004)
Borrelia burgdorferi is the causative agent of Lyme disease. Serum-resistant strains of the pathogen are able to reduce the host's immune response to infection by recruiting fluid-phase complement regulators from the serum. B. burgdorferi complement regulator-acquiring surface protein-1 (BbCRASP-1) binds factor H and factor-H-like protein-1 to the bacterial surface, where they actively down-regulate complement response. Crystals of native and selenomethionine-substituted BbCRASP-1 have been obtained and a native data set to 2.7 A as well as selenomethionine MAD data to 3.2 A resolution have been collected. The selenium substructure has been solved and initial phases have been refined to 3.0 A by density-modification methods. Model building and refinement are under way.
Gesehen am 26.02.2021